The Relationship Between Self-Control, Self-Awareness, And Cyberloafing Behavior On Guidance And Counseling Students In Universitas Bengkulu - Yunita Amiyaty Lubis; Yessy Elita; Rita Sinthia (G-Couns: Jurnal Bimbingan dan Konseling, 2025)
This study aims to describe the relationship between self-control and self-awareness with cyberloafing behavior in Bengkulu University Guidance and Counseling students. The sampling technique employed was simple random sampling. This research employs a descriptive, quantitative approach with correlational techniques, involving 106 students as subjects. Data analysis was conducted using multiple regression analysis with the aid of SPSS software version 26. The correlation coefficient value between self-control, self-awareness, and cyberloafing behavior is -0.549, indicating that as self-control and self-awareness decrease, cyberloafing behavior increases. So, it can be concluded that self-control has a negative and significant relationship to cyberloafing behavior, with a correlation coefficient of -0.556. While self-awareness has a negative and significant relationship to cyberloafing behavior, with a correlation coefficient of -0.540. Self-control and self-awareness have a negative and significant relationship to cyberloafing behavior, with a significant level of relationship. This research can inform actions to help students, such as implementing effective handling strategies, for those who exhibit high cyberloafing behavior. Keywords: self-control, self-awareness, cyberloafing behavior